Omega-3 fatty acid enriched chevon (goat meat) lowers plasma cholesterol levels and alters gene expression in rats - Ebrahimi, Mahdi; Rajion, Mohamed Ali; Goh, Yong Meng; Farjam, Abdoreza Soleimani (Hindawi Publishing Corporation, 2014)
In this study, control chevon (goat meat) and omega-3 fatty acid enriched chevon were obtained from goats fed a 50% oil palm frond diet and commercial goat concentrate for 100 days, respectively. Goats fed the 50% oil palm frond diet contained high amounts of -linolenic acid (ALA) in their meat compared to goats fed the control diet. The chevon was then used to prepare two types of pellets (control or enriched chevon) that were then fed to twenty-male-four-month-old Sprague-Dawley rats ( in each group) for 12 weeks to evaluate their effects on plasma cholesterol levels, tissue fatty acids, and gene expression. There was a significant increase in ALA and docosahexaenoic acid (DHA) in the muscle tissues and liver of the rats fed the enriched chevon compared with the control group. Plasma cholesterol also decreased () in rats fed the enriched chevon compared to the control group. The rat pellets containing enriched chevon significantly upregulated the key transcription factor PPAR- and downregulated SREBP-1c expression relative to the control group. The results showed that the omega-3 fatty acid enriched chevon increased the omega-3 fatty acids in the rat tissues and altered PPAR- and SREBP-1c genes expression.